The Influence Of Drug Promotion Techniques On Prescribing Decisions Among Physicians In Sana’a City, Yemen - Al-Areefi, Mahmoud Abdullah Hussein (2013)
The pharmaceutical industry invests heavily in promotion, and it uses a variety of promotional strategies to influence physicians’ prescribing decisions. The purpose of this study is to explore those factors used to influence physicians’ prescribing decisions and their role in decision-making process. Specifically, this study investigates the relationships between physicians and medical representative (MRs) and to identify physicians’ perceptions, beliefs and attitudes toward interactions with those MRs, and to explore the potentially modifiable factors influencing those interactions; to identify the main sources of information physicians use to obtain knowledge about new drugs and to explore how they influence physicians’ prescribing decisions; and to investigate the relationship of physicians’ characteristics and practice-setting factors with previous factors. This study was conducted in a step-wise approach. In the first phase, a qualitative research method was adopted to have an in-depth understanding of the phenomenon surrounding the nature and extent of drug promotion techniques. In the second phase, a quantitative method was applied using the cross-sectional. Research was conducted in Sana’a, Yemen. Physicians in public and private hospitals were surveyed. All instruments were tested for its reliability and validity measures.